Energy-based coefficient selection for digital watermarking in wavelet domain. (1st January 2013) - Jabeen, Fouzia; Jan, Zahoor; Jahangir, Farhana
The massive spreading of broadband networks and new developments in digital technology has made ownership protection and authorisation of digital multimedia a very important issue. The reason is the availability of powerful tools for editing, lossless copying and transmission of digital multimedia such as images. Image watermarking is now an effective solution for the problem of authentication and protection of copyrighted image content. In this paper, discrete wavelet transform (DWT)-based watermarking technique is proposed in which mean energy of the each of 32 × 32 block in the CH and CV subbands is calculated and range of coefficients that exceed the mean energy of the block are selected for watermark embedding. Watson perceptual distortion control model is considered to keep the perceptual quality of the image and genetic programming (GP) is used to provide optimum watermarking level for the selected coefficients. The results show that there is almost no difference between original and watermarked image demonstrating key feature of imperceptibility. The technique has been tested and proves to be effective against a set of malicious attacks.